PENINGKATAN KEMAMPUAN MENULIS TEKS RECOUNT MELALUI METODE MIND MAPPING - BARIYAH BARIYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Application of the Main Mapping Method to Improve Recount Text Writing Skills for Class X Science 5 Students at SMA Negeri 2 Bantul. This study aims to find out how the application of the mind mapping method can improve the ability to write recount texts for students of class X IPA 5 SMA Negeri 2 Bantul in Semester 2 of the 2019/2020 academic year. The subjects of this study were students of class X IPA 5 with a total of 36 students in one class, consisting of 13 male students and 23 female students. The data collection technique used in this research is observation. While the evaluation tool used is a written test in the form of writing recount text. The data analysis technique is using descriptive qualitative and descriptive quantitative. This research was conducted with a classroom action research design whose implementation procedure follows the basic principles of general action research. The procedure is a cyclical or recycling process, starting from the planning stage, the action implementation stage, the observation/evaluation stage, and the reflection stage. The implementation of this research was carried out in two cycles. The results showed an increase from the first cycle to the second cycle. Based on the research data in the first and second cycles, all indicators experienced an increase in success as expected and the results showed an increase in students' ability to write recount texts. The increase is indicated by the achievement of the average result of 69.42 with the percentage of student completeness 66.67% increasing to 94.44 with the percentage of completeness of students 94.44%. achieving completeness on the Minimum Completeness Criteria of 70. The research was carried out for two cycles because at the end of the second cycle the indicator of success of the action already fulfilled. Thus, it can be concluded that the mind mapping method can improve the ability to write recount texts for SMA N 2 Bantul students. ABSTRAKPenerapan Metode Main Mapping untuk Meningkatkan Kemampuan Menulis Teks Recount Siswa Kelas X IPA 5 SMA Negeri 2 Bantul. Penelitian ini bertujuan untuk mengetahui penerapan metode mind mapping dapat meningkatkan kemampuan menulis teks recount siswa kelas X IPA 5 SMA Negeri 2 Bantul Semester 2 Tahun Pelajaran 2019/2020. Subyek penelitian ini adalah siswa kelas X IPA 5 dengan jumlah keseluruhan siswa dalam satu kelas adalah 36 siswa, yang terdiri dari 13 siswa laki-laki dan 23 siswa perempuan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi. Sedangkan alat evaluasi yang digunakan adalah tes tertulis berupa menulis teks recount. Teknik analisis data adalah menggunakan deskriptif kualitatif dan deskriptif kuantitatif. Penelitian ini dilaksanakan dengan rancangan penelitian tindakan kelas yang prosedur pelaksanaannya mengikuti prinsip dasar penelitian tindakan yang umum. Prosedur tersebut merupakan suatu proses siklus atau daur ulang, yang dimulai dari tahap perencanaan, tahap pelaksanaan tindakan, tahap observasi/evaluasi, dan tahap refleksi. Pelaksanaan penelitian ini dilakukan sebanyak dua siklus. Hasil penelitian menunjukkan adanya peningkatan dari siklus pertama ke siklus kedua. Berdasarkan data hasil penelitian pada siklus pertama dan siklus kedua, semua indikator mengalami peningkatan keberhasilan sesuai dengan yang diharapkan dan hasil penelitian menunjukkan adanya peningkatan kemampuan siswa dalam menulis teks recount. Peningkatan ditunjukkan dengan pencapaian hasil rata-rata sebesar 69.42 dengan persentase ketuntasan siswa 66.67% meningkat menjadi 94,44 dengan persentase ketuntasan siswa 94,44%.mencapai ketuntasan pada Kriteria Ketuntasan Minimal 70.Penelitian dilaksanakan selama dua siklus karena diakhir siklus kedua indikator keberhasilan tindakan sudah terpenuhi. Dengan demikian dapat disimpulkan bahwa metode mind mapping dapat meningkatkan kemampuan menulis teks recount siswa SMA N 2 Bantul.